Evaluation of Inflammatory, Cardiac and Hematological Parameters in Hospitalized Children with COVID-19 - Damla Geçkalan; Rahmi Özdemir; Zülal Yılmaz; Onur Sivas; Yasin Yılmaz; Cemile Hilal Çelik (Cam & Sakura Medical Journal)
Objective: The relationship between clinical symptoms such as inflammatory and coagulation parameters, which are very common in adults, is still unclear in children with coronavirus disease-2019 (COVID-19). The aim of this study is to investigate the levels of inflammation and coagulation blood parameters and their correlation with pneumonia in COVID-19 pediatric patients. Material and Methods: One hundred thirteen hospitalized COVID-19 pediatric patients were included in this study retrospectively. All patients’ age, gender, number of hospitalization days, respiratory symptoms, laboratory parameters, thoracic computed tomography, polymerase chain reaction results were recorded. Patients were analyzed for pneumonia presence and absence. Results: Gender distribution was 53% female, 47% male. Median age was 11.4 years. Hospitalization length was 4.5 days. Chest tomography was performed on 90 patients with respiratory complaints or symptoms, and COVID-19 pneumonia was detected in 62 patients (68.8%). There was a statistically significant difference in the length of hospitalization, age, white blood cell and troponin values between the patients with COVID-19 pneumonia and those without pneumonia (p<0.001, p=0.008, p=0.048, and p=0.003, respectively). When multivariate analysis was performed for these parameters, the probability of pneumonia was found to be 1.17 times higher for every additional year of age. Elevation of fibrinogen and D-dimer was not found to be statistically significant (p=0.07, p=0.29, respectively). There was no statistical difference between coagulation and inflammatory parameters in children with COVID-19 pneumonia. No cardiac complications or thrombosis were observed. Conclusion: The finding that the risk of COVID-19 pneumonia increases with age draws more attention in terms of diagnosis and treatment. Coagulopathy was not detected in patients with COVID-19 pneumonia and no treatment is required. In addition, a detailed cardiac assessment is required in patients without COVID-19 pneumonia due to elevated troponin levels.